Pengaruh Kinerja Keuangan, Leverage, Sharia Compliance, Invesment Acound Holder dan Ukuran Perusahaan Terhadap Islamic Sosial Riporting: Studi pada Bank Umum Syariah 2020-2024 - Taufik Kurahman Kurahman; Rosydalina Putri; Anggun Okta Fitri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to examine the effect of Financial Performance (X1), Leverage (X2), Shariah Compliance (X3), Investment Account Holders (X4), and Company Size (X5) on Islamic Social Reporting (ISR) disclosure. Using panel data from Sharia-compliant companies for the 2020–2024 period, the sample was determined using purposive sampling and processed using Panel Least Squares (PLS) regression via EViews.The results of the hypothesis testing indicate that partially, Leverage (X2), Investment Account Holders (X4), and Company Size (X5) have a significant but negative effect on ISR (p < 0.05). This indicates that high liability burdens and asset scale tend to limit the scope of social reporting for the sake of cost efficiency and information risk mitigation. Conversely, Financial Performance (X1) and Shariah Compliance (X3) do not have a significant effect, indicating that profitability and Sharia compliance levels are not the primary determinants of social transparency policy in this study. These findings confirm the relevance of Signaling Theory, which views certain financial indicators as risk signals that limit voluntary disclosure. The research's implications suggest that management should reframe its view of ISR as a strategic investment to strengthen legitimacy and stakeholder trust amidst the company's dynamic financial situation.